Wage inequality: is there a role for minimum wage and trade union in an intangible economy? - Lee, Tom Lim (2021)
Wage inequality is the unequal distribution of wage pay in between skilled and unskilled workers. In view of the rise of intangible capital in this digitalisation era, it is suspected that wage inequality will further be widened under this background. Meanwhile in this study, the major focus will be on identifying the key factors of wage inequality and potential mechanisms to minimize this issue in 15 European Union countries from year 2008 to 2015. This study considers the use of disaggregated data on sectoral level. Studying sectoral level data can provide a way for national level policies to become more specific. This research uses the Generalized Method of Moments (GMM) dynamic panel data estimator. This method is used as it is able to capture the lag effects and to ensure the efficiency of the study. The result shows that relative demand of skilled and unskilled workers, merchandise trade as a percentage of GDP, real minimum wage, ratio of intangible assets to tangible assets and interaction term of share of intangible and union density are statistically significant in affecting wage inequality. One of the important implications from the findings is that trade union should exist as a remedy to minimize wage inequality in this era of intangible economy.